Cyber-Law: Is it adequate to prevent the menacing act of cyber-bullying and cyber-stalking? - Hanif Suhairi, Abu Bakar; Nor Azmi, Hj. Johari (Universiti Kebangsaan Malaysia, 2009)
Organized by The Centre of Excellence for the Education of Learner Diversity Faculty of Education (UKM), 26th - 27th August 2008 at Marriot Hotel, Putrajaya.